Low neutralizing antibody titers after asymptomatic or non-severe SARS-CoV-2 infection over a 6-month assessment period. Issue 5 (May 2022) - Lazor-Blanchet, C.; Zygoura, P.; Dafni, U.; Lamoth, F.; Tsourti, Z.; Lobritz, M.A.; Regina, J.; Grandbastien, B.; Fenwick, C.; Pantaleo, G.; Calandra, T.; Meylan, S.
Highlights: Patients with asymptomatic and mild SARS-CoV-2 infections are at risk of re-infection within the same year. Median neutralizing activity is significantly lower in asymptomatic than in symptomatic participants.